2009
DOI: 10.1108/14635770910936540
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of thesis research: a case study

Abstract: Purpose -The purpose of this paper is to investigate the process of the thesis research in the industrial engineering related master's programmes in Chalmers University of Technology for benchmarking implementation in Islamic Azad University, South Tehran Branch (IAU-STB), taking into consideration the different conditions of two universities and respective countries of Sweden and Iran. Design/methodology/approach -In this research, case study strategy was employed. In total, 17 thesis reports from 2003 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Comparing similar organizations based on a recognized set of standard indicators, gives also the essence of the benchmarking technique (Wait and Nolte, 2005), and more specifically partly describes one of the primary types of benchmarking used today, the performance benchmarking (Asrofah et al, 2010). It is worth noting that all definitions of benchmarking are based on the idea of evaluating the performance of an organized system by comparing it to exogenous entities (Shahalizadeh et al, 2009). The present study may stimulate, especially non-ISO 9001 certified companies, to adopt benchmarking not only by simply comparing the performance measures among companies but furthermore by understanding how company processes work, including observing and studying methods (Longbottom, 2000).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Comparing similar organizations based on a recognized set of standard indicators, gives also the essence of the benchmarking technique (Wait and Nolte, 2005), and more specifically partly describes one of the primary types of benchmarking used today, the performance benchmarking (Asrofah et al, 2010). It is worth noting that all definitions of benchmarking are based on the idea of evaluating the performance of an organized system by comparing it to exogenous entities (Shahalizadeh et al, 2009). The present study may stimulate, especially non-ISO 9001 certified companies, to adopt benchmarking not only by simply comparing the performance measures among companies but furthermore by understanding how company processes work, including observing and studying methods (Longbottom, 2000).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…According to Yin (1994), research strategy should be chosen as a function of the research situation, while both qualitative and quantitative methods involve weaknesses and strengths (Amaratunga et al, 2002). It is very important to get a persuasive research result, therefore the choosing of one or several suitable methods can be the vital part of the research work (Shahalizadeh, Amirjamshidi & Shahalizadeh, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative enquiry often takes the form of a case study. Referring to Merriam (1998), Shahalizadeh et. al.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, BM can be recognised as an all-around process of identifying, understanding and adopting exceptional practices from other organisations around the world to help a company to improve its outputs (Kumar et al, 2006). It remains as a learning process that deals with observing external performance, comparing them with internal values, identifying and bridging the gaps and investing in making upgrades (Massa and Testa, 2004;Shahalizadeh et al, 2009). Studies have shown that BM is used by organisations in all parts of the world (Gomes and Yasin, 2011;Joo et al, 2011;Lockamy, 2011;Moriarty, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…, 2006). It remains as a learning process that deals with observing external performance, comparing them with internal values, identifying and bridging the gaps and investing in making upgrades (Massa and Testa, 2004; Shahalizadeh et al. , 2009).…”
Section: Introductionmentioning
confidence: 99%